The Integrated Role Of Health Practice Professionals In The Saudi Healthcare System: Workforce Developments In The Era Of Vision 2030 (The Review of Diabetic Studies, 2024)
The Saudi healthcare system is undergoing a major change driven by demographic shifts, epidemiological transitions, and the national reform agenda outlined in Vision 2030. Essential to this reform is a diverse health workforce comprising clinical practitioners, allied health professionals, public health specialists, administrators, and technical support personnel. This article analyzes the collective roles of health practice professionals in Saudi Arabia, emphasizing cross-disciplinary collaboration, workforce development, and system sustainability. By adopting a systems-based perspective, the article draws attention to the key role of investment in human capital and professional integration in achieving high-quality, equitable, and optimized healthcare that corresponds with national strategic objectives.